Peran Pasar Modal dalam Meningkatkan Perekonomian di Indonesia - Rahmawati, Irma Laily; Sa’diyah, Jamilatu; Turani, Kinta Sarah Hanivatul Nimas (Journal of Economics and Social Sciences (JESS), 2023)
Introduction: Indonesia is a developing country that ranks 16th among the G20 countries in 2021 in its economic sector. Indonesia's economic sector is mainly driven by investment, an activity of the capital market. This study aims to analyze the role of the capital market in the Indonesian economy. Research Methods: This research method uses a qualitative method with a literature study approach whose data is from journals, books, and the internet. Results: The results showed that the capital market is a means to raise public funds to be channeled into productive activities, such as funds obtained from the capital market can be used for business development, expansion, additional working capital and so on. Conclusion: From this research, it can be concluded that the capital market is vital in developing the Indonesian economy because it is part of investment. Hence, the country has the capital to carry out development and production activities to improve the economy.